Fast gradient HPLC/MS separation of phenolics in green tea to monitor their degradation - Šilarová, Petra; Česlová, Lenka; Meloun, Milan (Elsevier Science, 2017)
The degradation of catechins and other phenolics in green tea infusions were monitored using fast HPLC/MS separation. The final separation was performed within 2.5 min using Ascentis Express C18 column (50 mm x 2.1 mm i. d.) packed with 2 mu m porous shell particles. Degradation was studied in relation to the temperature of water (70, 80, 90 degrees C) and the standing time of the infusion (up to 6 h). Along with chromatographic separation, the antioxidant properties of the infusions were monitored using two spectrophotometric methods. During staying of green tea infusion, the degradation of some catechins probably to gallic acid was observed. Finally, the influence of tea bag storage on antioxidant properties of green tea was evaluated. Rapid degradation of antioxidants after 3 weeks was observed. The principal component analysis, factor analysis and discriminant analysis were used for the statistical evaluation of obtained experimental data.
Rychlá gradientová HPLC/MS separace fenolických látek v zeleném čaji pro monitorování jejich degradace
Keywords: Green tea; Phenolic compounds; Antioxidant activity; Porous shell particles; Liquid chromatography/mass spectrometry; Principal component analysis; Factor analysis; Discriminant analysis; zelený čaj; fenolické látky; antioxidační vlastnosti; LC/MS; PCA; faktorová analýza; diskriminační analýza